Antidepressant efficacy and side effect burden: an updated guide for clinicians - Tatum Kutzer; Michelle Dick; Trevor Scudamore; Mark Wiener; Thomas Schwartz (BioExcel Publishing Ltd, 2020)
Antidepressant treatment has been evolving and changing since the 1950s following the discovery of the classic antidepressant treatments including tricyclic antidepressants and monoamine oxidase inhibitors. The heterogeneity of the disorder became apparent in the beginning when individuals remained symptomatic despite medication compliance. This spurred further research in order to understand the neurobiology underlying the disorder. Subsequently, newer medications were designed to target specific neurotransmitters and areas of the brain involved in symptom development and maintenance. Our original review article looked at both classic and modern antidepressant medications used in the treatment of major depressive disorder. This manuscript is an update to the original review and serves to provide clinicians with information about novel antidepressant medications, augmentation strategies with atypical antipsychotics, over-the-counter medications, as well as nonpharmaceutical treatments that should be considered when treating each individual patient who remains symptomatic despite treatment efforts